A study to assess the knowledge and attitude of parents of children with epilepsy - Manju, V M; Joshi, Poonam; Gulati, Shefali (Indian Journal of Child Health, 2015)
Objective: The objective was to evaluate the knowledge and attitude of parents of children with epilepsy toward the disease. Methods: In this cross-sectional, descriptive study, parents of 60 children with epilepsy from pediatric neurology clinic of All India Institute of Medical Sciences were enrolled. Data on epilepsy were collected using pre-tested and validated self-developed knowledge, belief, and attitude questionnaire (?=0.85, 0.89). Results: The mean knowledge and attitude scores of parents of the children with epilepsy were9.82±3.9 (2-22) and 31.25±9.27 (0-40), respectively. Parents of the children with epilepsy had poor 50 (83.3%, scores